De-industrialisation of Maribor: From Devaluation to Subordinated Re-integration Into Global Capitalism - Podvršič, Ana (Journal for Geography, 2023)
We analyze the restructuring of the Maribor industry during the 1980s and 1990s. Various scholars have already studied the (de)industrialisation dynamics of Maribor in that period. We complement the existing studies by contextualizing the industrial transformations of the Maribor landscape within broader historical trends shaped by the neo-liberalisation of the world economy and the reintegration of the (post-)socialist economies from Eastern Europe into global capitalism under the Washington Consensus. Looking at the initial phase of the transition of Slovenia from the perspective of the Maribor region, one could see that it was all but “smooth and peaceful”.
Keywords: Maribor; neo-liberalism; Washington Consensus; (de)industrialisation; crisis; post-socialist transition